ANALYSIS OF PRODUCT DEVELOPMENT ROLE OF VOLUME SALES IN PT.PANASONIC GOBEL INDONESIA IN BATAM - Nila Krisnawati; Tibrani Tibrani; Ferry Muliadi Manalu (BENING, 2014)
Research on the analisys of the role of product development to sales volume  in PT.Panasonic Gobel Indonesia in Batam implemented by developing old products into new products. This research was done because the condition of the ever-changing customer tastes along with the development of technology. By doing research using colleration and regretion analisys is expected to increase sales volume and are able to extend the life cycle of product.The results showed that product development is done through the division of research and development (R D) provides a strong influence on the increased sales volume. The CRT television absolete and began to anbandoned by the consumer develop a LCD television that has features that is more sophisticated than the CRT TV. With the advent of new products that have better quality, consumer are beginning to switch to another brand of television began to re-purchase the product brand name “Panasonic”. Apart form product development through increased sales volume is also influenced by other factors such as pricing, advertising and promotion, quality and service.